ANALISIS KOMPARASI USAHATANI PADI DARAT DAN PADI SAWAH DI DESA BATU SUMBANG KECAMATAN SIMPANG JERNIH KABUPATEN ACEH TIMUR - Mira Lestari; Muhammad Jamil; Supristiwendi, Supristiwendi (Bajang Institute, 2023)
This study aims to find out the income of land-based rice and paddy fields in Batu Sumbang Village, Simpang Jernih District, East Aceh Regency and compare these income so that it is known which type of rice is more profitable. This research was conducted in Batu Sumbang Village, Simpang Jernih District, East Aceh Regency. The result of this study is that the average income of land rice is Rp.5.378.922 (Rp/MT/Ha) while the average income of paddy rice is Rp.5.604.249 (Rp/MT/Ha). Based on the results of the analysis conducted using the Independent Simple T Test, it is known that the sig value. (2 tailed) is 0.635, meaning that the value is smaller than 0.05 (0.635>0.05) then there is no difference between the income of land rice and lowland rice